Pengembangan Media Pembelajaran Berbasis Video Animasi pada Pembelajaran Tematik Muatan Bahasa Indonesia Kelas III SD - Khairunnisaa, Sri; Kartono, Kartono; Salimi, Asmayani (AS-SABIQUN, 2023)
This research intends to develop media products in teaching and learning activities in the form of animated videos made for thematic learning of Indonesian language content for class III elementary schools that meet the requirements to assist teaching and learning activities in the 2013 curriculum. This research method is an RnD method with the model is ADDIE. The research data was obtained by involving 23 grade III students of 28 Pontianak City Public Elementary School, 1 class teacher, and 2 expert validators consisting of 1 media expert and 1 language and material expert. Techniques for collecting data in this study are observation and questionnaires. The results after the research show that the process of developing instructional media in the form of animated videos in Indonesian language content thematic learning activities in class III Elementary Schools has taken 3 stages of the ADDIE model research from the 5 stages. The validity of animated video products produces very good criteria with an average score of 95% for the design aspect, 94.4% for the language aspect, and 92.5% for the material aspect. So this animated video-based learning media in the thematic learning of Indonesian language content for class III Elementary School is feasible to use and try out at the next stage.